PENERAPAN MODEL STRINGER (LOOK-THINK –ACT) DALAM PEMBERDAYAAN PEREMPUAN DISABILITAS DI BOGOR - Titi Nurhayati purba; Dedes Fitria; Yohana Wulan rosaria (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2022)
In Indonesia, as an effort to alleviate poverty, the Ministry of Social Affairs in Indonesia has programs with target groups such as 'Persons with Social Welfare Problems (PMKS)-social welfare problems including the Group of Socioeconomically Vulnerable Women (WRSE) including  women in  the disability group.there is limited access to information to develop themselves. The solutions offered are to increase knowledge about reproductive health, especially about preventing the transmission of sexually transmitted infections and HIV AIDS, improve skills in making crafts from fabric waste and making healthy snacks. The coaching method is to apply the Stringer model with the  Look-Think Act stage  to form a class of 20 people as Mitra I and Mitra II  consisting of 20 people.  Participants were given material and practice by means of discussions, question and answer lectures, role play, brainstroming and demonstrations. The activity was carried out for 2 semesters consisting of: initial activities carried out at the Bogor City Disability Foundation. The output of activities is Services including health education and skills to participants so that they are able to carry out  the skills taught so that women have readiness and apply a healthy life style,  and improve the economy, take advantage of free time to increase socialization and togetherness between   WRSE . The response from the participants was very enthusiastic about this activity, the community has the motivation to develop and improve its economy to make snacks for their own use and can be sold to increase their income